A economia da região portuária do Rio de Janeiro (1870-1900) - Cezar Honorato (Centre de Recherches sur les Mondes Américains, 2016)
The purpose of this article is to discuss the development of a set of economic activities related directly or indirectly to the port activities in the city of Rio de Janeiro in the last quarter of the nineteenth century, before, so the port reform (1903-1910). To do this, we start from the idea of setting up a Port Economic Community involving direct from operators in a port of the old type (wharfs, freight transport, “trapiches”, etc.), import and export companies, shipping companies and banks linked to the sector, in addition to supporting industries, which depended on imported inputs, and other commercial activities that have developed in the region forming a real "economic necklace". For the purposes of this article we will consider only those projects installed in Rio port area to be clearly spelled out in the text. The sources used are quantitative and qualitative arising from board of trade funds, the National Archives, National Library, General Archive of the city of Rio de Janeiro.